2018
DOI: 10.1080/02701367.2018.1442915
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences Influencing Immediate Effects of Internal and External Focus Instructions on Children’s Motor Performance

Abstract: Children can benefit from instruction with both an internal and external focus of attention to improve short-term motor performance. Individual, task-specific focus preference influenced the effect of the instructions, with children performing better with their preferred focus. The results highlight that individual differences are a key factor in the effectiveness in children's motor performance. The precise mechanisms underpinning this effect warrant further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Our results demonstrated that working memory did not predict the extent to which motor learning had occurred, neither after internal focus instructions, nor after external focus instructions. These results are consistent with previous research showing a lack of effect of working memory on motor learning of a golf putting task in general (Brocken et al, 2016;van Abswoude et al, 2018). Together these results question the role of working memory capacity for motor learning in general and more specifically for motor learning with an external versus an internal focus of attention.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results demonstrated that working memory did not predict the extent to which motor learning had occurred, neither after internal focus instructions, nor after external focus instructions. These results are consistent with previous research showing a lack of effect of working memory on motor learning of a golf putting task in general (Brocken et al, 2016;van Abswoude et al, 2018). Together these results question the role of working memory capacity for motor learning in general and more specifically for motor learning with an external versus an internal focus of attention.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, verbal answers on the manipulation check were explored following the procedure of Perreault and French (2016) and van Abswoude et al (2018). The answers of the participants were divided into multiple fragments that were coded separately using the coding scheme that is displayed in Table 2.…”
Section: Manipulation Checkmentioning
confidence: 99%
See 2 more Smart Citations
“…attentional focus on instructions could be modulated by individual differences and preferences, but to our knowledge gender preferences have not been investigated. 21 Future studies should investigate how women and men improve SM skills according to various teaching approaches and strategies.…”
Section: Gender Effectmentioning
confidence: 99%